An Agrobacterium‐mediated base editing approach generates transgene‐free edited banana - Van den Broeck, Senne; Ngapout, Yvan; Panis, Bart; Vanderschuren, Hervé (Wiley, 2025)
Genome editing for the development of improved varieties is supported by the possibility of segregating out the editor T-DNA cassette after genome editing in many crop species. Removal of the T-DNA cassette prevents potential continuous editing activity in the transformed plant and furthermore facilitates regulatory approval. While transgene outcrossing of exogenous sequences is possible for many crops, this is not the case for vegetatively propagated and sterile crops, such as Cavendish bananas. Therefore, gene editing techniques leading to transgene-free edited plants are essential to untap the potential of genome editing for those crops. Here, we present a method for transgene-free gene editing in sterile banana (Musa spp.) through a co-editing strategy. A novel Agrobacterium tumefaciens-mediated transgene-free gene editing approach combining embryogenesis and chlorsulfuron selection was established in sterile banana and validated through whole genome sequencing. Editing of the acetolactate synthase (MaALS) genes in banana using a plant base editor allows effective selection of edited plants. Moreover, transgene-free plantlets were regenerated with mutations at two target sites, indicating that the strategy can be used to target multiple genomic sites. The presented method allows for efficient transgene-free gene editing and represents the first report of a co-editing strategy in sterile crop species.